Effect of Ramadan intermittent fasting on aerobic and anaerobic performance and perception of fatigue in male elite judo athletes - Chaouachi, A.; Coutts, A. J.; Chamari, K.; Wong, D. P.; Chaouachi, M.; Chtara, M.; Roky, R.; Amri, M. (The Journal of Strength and Conditioning Research, 2009)
The aim of the present study was to evaluate the influence of the Ramadan intermittent fast (RIF) on aerobic and anaerobic exercise performance in elite judo athletes (Judokas) maintaining their usual training loads. Physical performance tests (squat jump [SJ]), countermovement jump [CMJ], 30-second repeated jump, 30-m sprint, and the multistage fitness test) and fatigue scores were measured in 15 elite Judokas on 4 occasions: before Ramadan (T1), at the beginning of Ramadan (T2), at the end of Ramadan (T3) and 3 weeks after Ramadan. Results showed that 30-m sprint performance, multistage shuttle run test, SJ, and CMJ did not change during Ramadan. However, average power during the 30-second repeated jump test was slightly lower at the end of Ramadan (22.4 ± 2.3 W/kg; P < 0.05) than before Ramadan (23.4 ± 2.3 W/kg). There was a minor reduction of 1.3 kg in body mass and an increase in total fatigue scores (T2, 19 ± 5; T3, 16 ± 4; both P < 0.05) during Ramadan in comparison with the control period (T1, 12 ± 3). These results show that the RIF has little effect on aerobic performance and on very short duration sprinting and jumping test performance in elite Judokas. Additionally, experienced athletes can maintain both sufficient energy intake and normal training loads during the RIF. The slight reduction in the 30-second jump test may be associated with reduced central drive and body mass. Collectively, these results suggest that the RIF has little effect on the performance of experienced Judokas, but Muslim athletes who train during the RIF should carefully periodize their training load and monitor their food intake and fatigue levels to avoid performance decrements.